Optimisation of Neon sxr (Soft x-ray) Yield of the INTI Plasma Focus Machine at 12 kv - Federico, A. R. J. A.; Chong, P. L.; Saw, S. H. (School of Engineering,Taylor’s University, 2015)
The INTI plasma focus machine is a 3 kJ Mather type plasma focus machine,powered by a single Maxwell capacitor. The system produces remarkable consistent focusing action in neon, making it a suitable source for the production of high energy photons, electrons, ions and neon soft x-rays (SXR). The aim of this paper is to optimise the neon SXR yield of the INTI plasma focus machine operated at 12 kV by parametrically, changing the anode dimensions (radius and length) using the Lee Model Code (version RADPFV5.15dd). Results of the optimisation procedures resulted in a neon SXR yield of 6.47 J at 2.5 torr and 12 kV, with a shorter length and a fatter anode radius of 7.9 cm and 1.2 cm respectively. This gives an improvement in the neon SXR yield of 40% when compares to neon SXR yield of 2.74 J at 2.5 torr 12 kV with the present configurations.